Optimalisasi Supervisi Akademik sebagai Upaya untuk Meningkatakn Kinerja Guru dalam Menerapkan Model Pembelajaran Contextual Teaching and Learning (CTL) di SDN 58/X Teluk Majelis Tahun Ajaran 2021/2022 - Peri Peri (Journal on Education, 2022)
This study aims to obtain information and discuss academic supervision as an effort to improve teacher performance in implementing the contextual teaching and learning (CTL) learning model at SDN 58/X Teluk Majelis. This research is school action research which consists of two cycles by following four stages, namely planning, implementation, observation, and reflection. This research was carried out at 58/X Teluk Majelis with the subject of 16 teachers consisting of class teachers and subject teachers which took place in the odd semester of the 2021/2022 academic year. Data were collected using observation sheets, field notes and documentation and analyzed using percentages and data reduction. The results show that academic supervision can improve teacher performance in implementing the contextual teaching and learning (CTL) learning model at SDN 58/X Teluk Majelis by giving rewards.